Attitudes towards frailty assessment in clinical practice among psychiatrists in the UK. Issue 4 (28th November 2019) - Anantapong, Kanthee; Tinker, Anthea
Abstract : Purpose: Although there is substantial evidence about the association between frailty and mental illnesses in older people, there is currently little evidence about how this is integrated into psychiatric clinical practice. The purpose of this paper is to explore the attitudes of a sample of psychiatrists in the UK about the concept and assessment of frailty in their clinical practice. Design/methodology/approach: This research used a qualitative approach with semi-structured interviews. Interview schedules and transcripts were analysed using thematic analysis. NVivo software and an audit trail were used for the data analysis. Findings: There were ten respondents (all psychiatrists) in this study. From the interviews, it appeared that some respondents were not be fully familiar with existing concepts of frailty. However, from their perspectives, frailty appeared to be multidimensional, reversible and for some could be enhanced by older people's ability. Negative stereotypes of being frail could undermine the accessibility to appropriate assessment and care. Existing multidisciplinary assessments, with some adjustments to the particular needs of psychiatric patients, can be used to establish a frailty index. Originality/value: The concept of frailty, especially those concerning its multidimensional and homeostatic nature, should be further examined to make it more applicable to psychiatric practice. Without much more effort, frailty could be assessed within current psychiatric practices. This could constitute a care plan tailored for frail people with a psychiatric illness, so as to improve the outcomes of their treatment and quality of life.